Prevalence and risk factors of sleep apnea in adult patients with congenital heart disease. (May 2019) - Harada, Gen; Takeuchi, Daiji; Inai, Kei; Shinohara, Tokuko; Nakanishi, Toshio
Abstract: Background: Although sleep apnea is an important disorder associated with cardiac events, data regarding its prevalence and risk factors in adult patients with congenital heart disease are limited. Methods: In this study, patients underwent a sleep study in the hospital. Indications for admission were classified as heart failure, diagnostic catheterisation, interventional catheterisation, or arrhythmia. The prevalence, characteristics, and risk factors of sleep apnea using a type-3 portable overnight polygraph in adult patients with congenital heart disease were evaluated. Results: There were 104 patients [median age: 36 (interquartile range: 28–48) years] who were admitted for heart failure 34% (n = 36), diagnostic catheterisation 26% (n = 27), interventional catheterisation 18% (n = 19), or arrhythmia 22% (n = 23). The prevalence of sleep apnea, defined as a respiratory disturbance index ≥5, was 63% (n = 63), with a distribution of 37%, 16%, and 10% for mild (5≤ respiratory disturbance index <15), moderate (15≤ respiratory disturbance index <30), and severe (respiratory disturbance index ≥30) sleep apnea, respectively. A large majority of the sleep apnea cases were categorised as obstructive sleep apnea (92%, n = 58). The respiratory disturbance index ≥15 group had a significantly higher proportion of male patients and higher body mass index, noradrenaline level, and aortic blood pressure than the group without sleep apnea (respiratory disturbance index <5). Multivariable analysis showed that New York Heart Association class ≥II (OR, 4.36; 95% CI, 1.09–20.87) and body mass index ≥25 (OR, 4.29; 95% CI, 1.32–15.23) were independent risk factors for a respiratory disturbance index ≥15. Conclusion: Our results showed a high prevalence of sleep apnea in adult patients with congenital heart disease. Its unique haemodynamics may be associated with a high prevalence of sleep apnea. Congestive heart failure and being overweight are important risk factors for sleep apnea. Management of heart failure and general lifestyle improvements will be important for controlling sleep apnea symptoms in these patients.